Distributions of the Pelagic Holothurian Pelagothuria in the Central Pacific Ocean as Observed by Remotely-Operated Vehicle Surveys - Selig, Gina M.; Netburn, Amanda N.; Malik, Mashkoor (Frontiers in Marine Science, 2019)
Pelagothuria is the only known genus of holothurian that is considered to be holopelagic. There is thought to be only one species, Pelagothuria natatrix, and little is known about its abundance and distribution throughout the global ocean. Most documented observations of Pelagothuria are in tropical regions with many in or near water masses with low dissolved oxygen concentrations, suggesting that Pelagothuria may be associated with oxygen minimum zone regions. During the spring 2017 NOAA Ship Okeanos Explorer Mountains in the Deep Expedition, scientists onboard the ship and participating through telepresence noted seeing an exceptional number of Pelagothuria during ROV dives conducted at sites along a transit from Pago Pago, American Samoa to Honolulu, Hawaii. Video from all dives was later reviewed using the video replay and annotation tool SeaTube and Pelagothuria were seen at 9 of the 12 ROV dive sites explored. A total of 97 Pelagothuria were observed in depths ranging from 196 to 4,440 m, temperatures of 1.3–15.4°C, salinities of 34.5–35.2, and oxygen concentrations of 0.17–3.77 mg L−1. The vertical distribution of Pelagothuria averaged 865 m depth, and their observations occurred at means of 5.24°C, 34.56, 1.71 mg L−1 for temperature, salinity, and dissolved oxygen, respectively. In 30 percent (n = 27) of the occurrences of Pelagothuria, the organism was observed at or within site of the seafloor, suggesting that the species may not actually be entirely holopelagic. A literature review was also conducted to look at the biogeography of the taxon. Results suggest that the horizontal distributions of Pelagothuria may extend to the Equatorial Pacific region, and the relatively high occurrence of Pelagothuria in oxygen minimum zones indicates they may be particularly hypoxia-tolerant. There is some indication that Pelagothuria may also be associated with areas of high particle flux. The strong El Niño event that occurred shortly before the expedition and anomalously warm conditions throughout much of the Pacific could have provided conditions favorable to a Pelagothuria bloom, however the high abundances of the organism seen on a nearby 2015 expedition and a later 2019 expedition suggest that this may be a persistent feature. The water column in this region has never before been explored with ROVs, and this study demonstrated use of an archived and publicly-accessible exploratory dataset to make novel discoveries.